Penerapan Best Practice IT Service Management dalam Perbaikan IT Service Desk: Studi Kasus PT. Matahari Putra Prima - Hendra, Hendra (Bina Nusantara University, 2011)
Information Technology (IT) grows very rapidly and affects every aspect of business life to support competition with other companies that have the same field. PT. Matahari Putra Prima has implemented a computerized system as one of its business strategy in achieving the company's business objectives. With the implementation of IT in the company, the role of Service Desk is indispensable in providing services to users. This study aims to identify and analyze the implementation of IT Service Desk of PT. Matahari Putra Prima to the users. This research is expected to increase and improve the quality of IT Service Desk PT. Matahari Putra Prima based on the IT Service Management (ITSM).